The role of process variables in the design of multiproduct batch protein production plants - Montagna, Jorge Marcelo (2001)
This work reports findings about the role of process variables in the design of multiproduct batch plants. Unlike continuous processes, batch processes are subject to size and time constraints which depend on the structure of the plant: the number of units at each stage and the provision of intermediate storage. We used simple process performance models (yet involving all the process variables with significant economic impact) to get explicit expressions for these size and time factors. The traditional approach uses fixed size and time factors. So the addition of those expressions to the original fixed factors model, permitted to simultaneously optimize the plant structure and process variables, and study the role of the latter in the design. We found that if the plant structure constraints are disregarded (with a Free Unlimited Storage operating policy), process variables behave just alike in continuous processes. They trade off cost components with the Total Annual Cost being quite insensitive to them in the neighborhood of the optimal solution. As setting the process variables sets the size and time factors, this means that near the optimal set of process variables, cycle times and size factors can be accommodated to the plant structure, with little effect on the cost of equipment.